Solve the following simultaneous equations by using Cramer's rule: 3x – y = 7 & x + 4y = 11

2. Solve the following simultaneous equations by using Cramer's rule:
3x – y = 7  & x + 4y = 11

Answer. The given equations are 3x – y = 7  & x + 4y = 11


D =
3
-1
=
(3 × 4) – (1 × - 1)
=
12 + 1
=
13




1
4











Dx =
7
-1
=
(7× 4) – [11× (-1)]
=
28 + 11
=
39




11
4










Dx =
3
7
=
(3×11) – [1× 7]
=
33 - 7  
=
26




1
11










By Cramer's Rule







x
=
Dx
=
39
=
3



D

13



















y
=
Dy
=
26
=
2



D

13





No comments:

Post a Comment